Peningkatan Public Speaking Skill Melalui Pendekatan POBC dan Mind Mapping Bagi Mahasiswa Universitas Teuku Umar - Yuhdi Fahrimal; Asmaul Husna; Johan Johan; Farina Islami (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Pubic speaking is an individual skill that is a necessity in the current era of disruption. Public speaking skills are needed to support the best results in education, the social environment, and the workplace. But not everyone is able to do public speaking well. Previous research states that the condition is caused by excessive fear of individuals to speak in front of the crowd (glossophobia). The objectives of this training are (1) to open students' horizons about public speaking; (2) arousing student motivation so as not to worry about public speaking; and (3) train students practically to be able to practice public speaking in everyday life. This training uses three stages, namely, pre-training research, lectures and discussions, and the practice of public speaking. The results of the training provide practical public speaking techniques to students with a simple concept known as POBC namelyPlanning, Opening, the Body of Speech, and Conclusion and mind mapping. This method is considered to make it easier for students to do public speaking systematically from planning to closing interesting speeches.